ASSET MANAGEMENT AND FIRM VALUE OF LISTED OIL AND GAS FIRMS IN NIGERIA (Journal of Global Accounting, 2025)
The study examined the effect of asset management on the firm value of listed oil and gas firms in Nigeria. The specific objectives are to: examine the extent to which current asset turnover ratio affects the Tobin’s Q of listed oil and gas firms in Nigeria; determine the extent to which fixed asset turnover ratio affects the Tobin’s Q of listed oil and gas firms in Nigeria, and ascertain the extent to which total asset turnover ratio affects the Tobin’s Q of listed oil and gas firms in Nigeria. Research questions and hypotheses were formulated in line with the objectives of the study. Ex-Post Facto research design was adopted. The sample of the study consists of nine listed Oil and Gas firms on the Nigerian Exchange Group (NGX). Data were extracted from the companies of the study annual reports and accounts from 2014 to 2023. Analysis was carried out with regression analysis. The study revealed that Current Asset Turnover Ratio has a positive but non-significant effect on Tobin's Q of listed oil and gas firms in Nigeria (Beta: 0.091155, p = 0.5286); Fixed Asset Turnover Ratio has a positive but non-significant effect on Tobin's Q of listed oil and gas firms in Nigeria (Beta: 0.000762, p = 0.8140), and that Total Asset Turnover Ratio has a negative but non-significant effect on Tobin's Q of listed oil and gas firms in Nigeria (Beta: -0.222383, p = 0.3378). The study recommended among others that management teams of listed oil and gas firms enhance their current asset management practices to improve efficiency by adopting more sophisticated inventory management systems and optimizing working capital, thereby driving higher revenue generation from current assets..
Keywords: : Asset management; Current asset turnover; Fixed asset turnover; Tobin’s Q